UJI AKTIVITAS ANTIMIKROBA EKSTRAK KULIT BUAH NAGA (Hylocareus costarisensis) TERHADAP E.coli, Staphylococcus aureus, DAN Candida albicans - Shinta, Dewi Yudiana; Hartono, Adi (Sainstek : Jurnal Sains dan Teknologi, 2017)
Hylocareus costarisensis more commonly known as red dragon fruit are beneficial as antioxidant and a source of natural pigments and potentially as antimicrobial. Journal of Food Research points out that the content of Phenol in the peel of red dragon fruit is greater than the the red dragon fruit itself.  Phenol contained in the dragon fruit peel can be useful as antimicrobial because it can lower the surface tension of the microbial. This study therefore aims to figure out whether there is an effect the phenol of Red Dragon Fruit Peel (Hylocareus Costarisensis) extract on the ability to block the growth of microbial patogent such as E.coli, Staphylococcus aureus, and Candida albicans and to figure out the compounds found in in the dragon fruit peel . This research employs statistical analysis experiment design by using One Way ANOVA test. The concentration of Red Dragon Fruit Peel extract used was 0,4 gr, 0,8 gr, 1,4 gr, 1,8 gr, 2,0 gr and positive control concentration thinning microbial 1,8 x 103Cell/ml. These studies demonstrated that the antimicrobial compounds in extract of  Red Dragon Fruit Peel is Acetic Acid, Formic Acid and Phenol. This research also indicates that the bigger dose of Red Dragon Fruit Peel, the greater power ability to block the growth. The ability to block the growth of microbial is statistically significant (p< 0,05) after giving of Red Dragon Fruit Peel extract